The civilisational and cultural heritage of Iran and the Malay world a cultural discourse - Farid Alatas, Syed; Alami, Abdolreza (Gerakbudaya Enterprise, 2018)
The development of Islamic civilisation in the various regions of the world was, and is, a complex process which has attracted the attention of many researchers. The Muslim world can be compared to an Iranian carpet which, with its diversity of colours, geometrical patterns and floral designs, symbolises its very unity in diversity. The Muslim world has a mesmerising diversity of cultures, languages, ethnicities, and religious sects, and yet cannot be looked upon except through the lens of unity, a principle which lies at the heart of the Islamic religion. This is true despite the sectarianism that afflicts Muslims today. The chapters which make up this volume were originally presented at the 'International Conference on the Civilisational and Cultural Heritage of Iran and the Malay World: A Cultural Discourse', jointly organised by the Cultural Centre of the Islamic Republic of Iran in Malaysia, the Asia West East Centre (Asia WE), the Faculty of Arts and Social Sciences, University of Malaya, the Department of Malay Studies, National University of Singapore, and the University of Nottingham Teaching Centre. They aim to chronicle this unity in diversity of the Islamic world with a focus on the historical relations and interactions between the Persian and Malay world, Persian linguistic influence on the Malay language, the impact of Persian music in the Malay world, Sufi connections between the Iranian and Malay worlds, the Persian roots of classical Malay political thought, representations of Iran in Malaysia, and the importance of cultural dialogue between the Persian and Malay worlds.